Plants of oceanic islands : evolution, biogeography, and conservation of the flora of the Juan Fernandez (Robinson Crusoe) Archipelago - Stuessy, Tod F. (Cambridge University Press, 2018)
Bringing together results from over 30 years of research on the Juan Fernández Archipelago off the coast of Chile, this book offers comprehensive coverage of the plants of these special islands. Despite its remote setting in the southeastern Pacific Ocean, the Juan Fernández Archipelago is in many ways an ideal place to ask and attempt to answer basic questions regarding the evolution of vascular plants in an oceanic island environment. By building upon a firm taxonomic base for the flora, a new level of understanding regarding evolution, biogeography, and conservation of the plants is presented. This book is an extensive investigation of the origin and evolution of the flora of an oceanic archipelago, and it serves as a valuable resource for researchers and scholars of island biology as well as for conservation biologists worldwide.